Nephtyidae (Annelida, Polychaeta) from southern Europe - Ravara, Ascensão (2012)
Eighteen nephtyid species belonging to four different genera are known from southern Europe. In this study we revise the nephtyids from this area and provide descriptions of all the known species. Geographical and bathymetrical distributions are given, together with ecological notes. Inermonephtys foretmontardoi, new species, is described, Micronephthys maryae is newly synonymized with M. stammeri and Aglaophamus rubellus with A. agilis. New diagnoses are provided for southern European genera and a key to all species from the region is included.